Enantioselective total synthesis of (R)-(−)-complanine - Kamanos, Krystal A. D.; Withey, Jonathan M. (My University, 2012)
A route is described for the enantioselective synthesis of (R)-(−)-complanine, a marine natural product isolated from Eurythoe complanata, and known to be a causative agent in inflammation. An organocatalytic, asymmetric oxyamination of a homoconjugated all-Z-dienal intermediate provides versatile and efficient access to the natural product.
Keywords: complanine; enantioselective synthesis; marine fireworm; nitrosoaldol; organocatalysis